A highly efficient LaOCl supported Fe–Fe3C-based catalyst for hydrogenation of nitroarenes fabricated by coordination-assisted pyrolysis. Issue 13 (9th June 2021) - Li, Xuewei; She, Wei; Wang, Jing; Li, Weizuo; Li, Guangming
Abstract : A highly efficient LaOCl supported Fe–Fe3 C-based catalyst derived from bi-MOFs prepared by coordination-assisted pyrolysis for hydrogenation of nitroarenes to arylamines. Abstract : Bi-metal–organic framework (bi-MOF) derived carbon-based catalysts have exhibited considerable potential for hydrogenation reactions; however, designing suitable bi-MOFs to fabricate highly efficient catalysts is still a great challenge. Herein, an efficient LaOCl supported Fe–Fe3 C-based carbon–nitrogen catalyst (Fe–Fe3 C-LaOCl/CN-hmta) was first prepared by bi-MOF (La–salen Fe@HMTA )-templated pyrolysis. La–salen Fe@HMTA was synthesized via the coordination-assisted method, e.g., it is prepared by the coordination of N from the rich free imine (–CHN–) groups located on the La–salen complex to the Fe 3+ ions from Fe@HMTA. Catalytic experiments reveal that Fe–Fe3 C-LaOCl/CN-hmta as a hydrogenation catalyst exhibits excellent performance for hydrogenation of nitroarenes in comparison with catalysts derived from Fe–urea MOFs (Fe–Fe3 C-LaOCl/CN-urea) and Fe(NO3 )3 ·9H2 O derived catalysts (Fe–Fe3 C-LaOCl/CN). On the basis of the nature of Fe–Fe3 C-LaOCl/CN-hmta and the reaction results, it is concluded that the unique catalytic efficiency of Fe–Fe3 C-LaOCl/CN-hmta depends significantly on the synergistic effect of Fe and Fe3 C, large specific surface area and abundant structural defects. This piece of research provides a new approach for preparing highly efficient and stable Fe–Fe3 C-based catalysts for hydrogenation of nitroarenes via the coordination-assisted pyrolysis (CAP) method.